Seychelles : First Review Under the Stand-By Arrangement, Request for Waivers of Nonobservance of Performance Criteria, and Financing Assurance Review; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Seychelles. (IMF Staff Country Reports; Country Report, 2009)
This paper discusses key findings of the First Review for Seychelles under the Stand-By Arrangement. Developments under the program at end-December 2008 were broadly satisfactory. Although growth was lower and inflation higher than targeted in 2008, the liberalization of the exchange regime and interest rate have removed the severe distortions weighing on the economy, and early signs of stabilization are apparent. The program targets for 2009 have been adjusted, primarily in light of the much more difficult external environment.